Relapse of Psychosis Status Post Meningioma Resection - Hamza Mohammad-Amin; Amber N. Edinoff; Haseeb A. Akuly; Prithvi Doppalapudi; Rita Horton; Anthony Sin; Donard Dwyer; City Mohammad Amin; Sana Shamim (Health Psychology Research)
A 53-year-old Caucasian female with a previous psychiatric history of bipolar I disorder and attention deficit hyperactivity disorder presented to the emergency department after endorsing 10-11 months of auditory and visual hallucinations, persecutory delusions, depression, anosmia, weakness of lower extremities, and headache. The patient described her auditory hallucinations as non-commanding voices talking to her about her family, her visual hallucinations as seeing "shadows and shapes," and her paranoid delusions as people coming after her. The patient had sustained a fall a week and a half earlier, requiring eight sutures to her posterior scalp. Her MRI of the brain showed a well-circumscribed 3.5 x 4.7 x 3.2 cm mass in the floor of the anterior cranial fossa. Computer tomography of the brain showed a 4.5 cm mass near the anterior interhemispheric fissure and edema in the right frontal cortex. Meningioma resection resulted in the cessation of hallucinations and delusions for one week. However, the patient was brought back to the emergency department because her auditory hallucinations and delusions returned. This case report demonstrates residual psychosis, even after frontal meningioma resection.